Is race medically relevant? A qualitative study of physicians' attitudes about the role of race in treatment decision-making - Snipes Shedra; Sellers Sherrill L; Tafawa Adebola; Cooper Lisa A; Fields Julie C; Bonham Vence L (BMC, 2011)
Abstract Background The role of patient race in medical decision-making is heavily debated. While some evidence suggests that patient race can be used by physicians to predict disease risk and determine drug therapy, other studies document bias and stereotyping by physicians based on patient race. It is critical, then, to explore physicians' attitudes regarding the medical relevance of patient race. Methods We conducted a qualitative study in the United States using ten focus groups of physicians stratified by self-identified race (black or white) and led by race-concordant moderators. Physicians were presented with a medical vignette about a patient (whose race was unknown) with Type 2 diabetes and untreated hypertension, who was also a current smoker. Participants were first asked to discuss what medical information they would need to treat the patient. Then physicians were asked to explicitly discuss the importance of race to the hypothetical patient's treatment. To identify common themes, codes, key words and physician demographics were compiled into a comprehensive table that allowed for examination of similarities and differences by physician race. Common themes were identified using the software package NVivo (QSR International, v7). Results Forty self-identified black and 50 self-identified white physicians participated in the study. All physicians - regardless of their own race - believed that medical history, family history, and weight were important for making treatment decisions for the patient. However, black and white physicians reported differences in their views about the relevance of race. Several black physicians indicated that patient race is a central factor for choosing treatment options such as aggressive therapies, patient medication and understanding disease risk. Moreover, many black physicians considered patient race important to understand the patient's views, such as alternative medicine preferences and cultural beliefs about illness. However, few white physicians explicitly indicated that the patient's race was important over-and-above medical history. Instead, white physicians reported that the patient should be treated aggressively regardless of race. Conclusions This investigation adds to our understanding about how physicians in the United States consider race when treating patients, and sheds light on issues physicians face when deciding the importance of race in medical decision-making.